Draft Annual Plan (2005-06) Proposals (Statement) Volume - II Government of Manipur - Planning Commission (Planning Commission, 2004)
Ongoing, E.A.P., Outlay for District Plan C.S.S., P.M.G.Y. Outlay / Expenditure T.S.P. (Financial) T.S.P. (Physical), S.C.P. (Financial) S.C.P. (Physical) Voluntary Sector (Outlay Expenditure).
Planning Department, Government of Manipur